Conditioning of raw sludge and thermally hydrolyzed sludge by ferric salt and cationic polyacrylamide: rheological analysis - Liqiang Duan (IWA Publishing, 2021)
In this study, the conditioning effect of cationic polyacrylamide (CPAM) with different charge densities on raw sludge (RS) and thermo-hydrolyzed sludge (HS) pretreated with or without ferric salt is studied through orthogonal experiments. In addition, this paper uses the principles of rheology and morphology to analyze and clarify the conditioning mechanism of RS and HS, and reveals the mechanism of thermal hydrolysis to improve the dewatering performance of sludge. Compared with the RS, the HS has smaller particle size, better filterability, stronger fluidity and more obvious thixotropy. However, due to the influence of filter pressing time, ferric salt should be added before conditioning. The orthogonal experiment shows that the optimal conditioner is CPAM with charge density of 60, and the specific resistance to filtration and capillary suction time of the adjusted thermo-hydrolyzed sludge are reduced to (1.11 ± 0.07) × 1012 m/kg and 16.1 ± 1.8 s; the particle size increased from 61.2 to 253.5 μm. The moisture content of the sludge cake is about 48%. The structural strength and thixotropy of HS are higher than those of the RS, and can be greatly improved by adding ferric salt. Morphological analysis confirms that thermal hydrolysis can lyse microbial cells in sludge, and the sludge treated with ferric salt will have more porous structure and stronger flocculation strength. HIGHLIGHTS Effects of CPAM on conditioning of raw sludge and thermal hydrolysis sludge were studied.; Thermal hydrolysis treatment will improve sludge dewatering capacity and fluidity.; Ferric salt treatment enhanced structural strength and thixotropy of conditioned thermal hydrolysis sludge.; Rheological analysis can be used as a new tool to reflect the dewatering capacity of sludge.;